Luminescence and a new approach for detecting heat treatment of geuda sapphire - T. Pluthametwisute; T. Pluthametwisute; L. Nasdala; C. Chanmuang N.; M. Wildner; E. Libowitzky; G. Giester; E. G. Zoysa; C. Jakkawanvibul; W. Suwanmanee; T. Sripoonjan; T. Tengchaisri; et al. (Solid Earth)
For decades, unraveling the heat treatment of sapphire has been a challenging issue. The present study offers new aspects that support the detection of heat treatment of sapphire. Natural geuda sapphire exhibits orange to red luminescence under longwave ultraviolet (LWUV; 365 nm) light, while heated geuda sapphire shows blue luminescence under shortwave ultraviolet (SWUV; 225 nm) light. The presence of melt inclusions in dissolved silks serves as an indicator of sapphire heat treatment. Fourier-transform infrared (FTIR) spectroscopy alone is insufficient for distinguishing unheated from heated sapphire. By combining orange to red luminescence with blue luminescence and melt inclusions, we provide a practical method for accurately differentiating natural gem-quality sapphire and heated gem-quality sapphire.